Problematic Internet Use in Undergraduate Health Science Students at a Remote Place of Nepal: A Cross-Sectional Study - Jha, Jay Prakash; Pun, Dilli Bahadur; Amgain, Kapil; Chaudhary, Hiramani Prasad (Journal of Karnali Academy of Health Sciences, 2023)
Background: Problematic internet use (PIU) is a growing concern among teenage and college students. Excessive internet use has detrimental effects on physical and mental health. This study aims to assess the computer usage pattern and calculate the frequency of PIU in undergraduate health science students at Karnali Academy of Health Sciences, Jumla, a remote place of Nepal.Methods: A cross-sectional questionnaire-based study was conducted from October to November 2022. Data were collected from all the undergraduate students who consented to participate. The questionnaire included students’ computer-related behaviours. PIU was defined as a score of 42 or above on the PIU questionnaire. Data were analyzed by descriptive and analytical statistics, keeping p value